Transitions to Post-School Life Responsiveness to Individual, Social and Economic Needs (Education in the Asia-Pacific Region: Issues, Concerns and Prospects, 2018)
This book addresses growing reservations about the relevance of educational systems to the economic and social needs of individuals by examining different aspects of transitions from school to work or further studies within formal and informal settings in Asia. Highlighting important issues such as selectiveness and inclusiveness, integration of transversal competencies, vocationalisation of secondary schooling, approaches to career guidance and emerging models of student support, it is of particular interest to educators, policymakers and other stakeholders who are concerned about the effectiveness of system-wide and institutional-based approaches. The first part of the book explores different models, mechanisms and approaches to policy and practice in the context of Asia, while the second part examines Hong Kong students' transitions to post-school life and provides an account of issues and challenges the government and individual schools experience in terms of structural support for both mainstream and special-needs students.